2011
DOI: 10.5665/sleep.1052
|View full text |Cite
|
Sign up to set email alerts
|

Time for Bed: Parent-Set Bedtimes Associated with Improved Sleep and Daytime Functioning in Adolescents

Abstract: Significant personal and public health issues, such as depression and accidental injury and mortality, are associated with insufficient sleep. Converging biological and psychosocial factors mean that adolescence is a period of heightened risk. Parent-set bedtimes offer promise as a simple and easily translatable means for parents to improve the sleep and daytime functioning of their teens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
163
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(176 citation statements)
references
References 24 publications
9
163
3
1
Order By: Relevance
“…These findings are in line with developmental research showing the absence of parental involvement in the decision-making of adolescents is related to an increase in behavior problems (Van Petegem et al 2012). This is particularly noteworthy since the percentage of adolescents who report having a parent-set bedtime steadily declines from 33 % at age 13 to 0 % at age 18 (Short et al 2011).…”
Section: Family Factorssupporting
confidence: 89%
See 2 more Smart Citations
“…These findings are in line with developmental research showing the absence of parental involvement in the decision-making of adolescents is related to an increase in behavior problems (Van Petegem et al 2012). This is particularly noteworthy since the percentage of adolescents who report having a parent-set bedtime steadily declines from 33 % at age 13 to 0 % at age 18 (Short et al 2011).…”
Section: Family Factorssupporting
confidence: 89%
“…Adolescents with parent-set bedtimes have earlier bedtimes and obtain more nighttime sleep and also experience less fatigue and improved daytime functioning (Short et al 2011). Adolescents with parent-set bedtimes of 10:00 p.m. or earlier are 24 % less likely to experience depression and 20 % less likely to have suicidal ideation in comparison to adolescents with parent-set bedtimes of midnight or later (Gangwisch et al 2010).…”
Section: Family Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither study reported whether parental or broader school inclusion was instrumental in changing sleep, but the behavior change literature and previous studies support parental involvement. 40 …”
Section: Community and Parental Inclusionmentioning
confidence: 99%
“…Obtaining more sleep has been shown to benefit daytime functioning in adolescents and positively influence mood, whereas sleep deprivation worsens mood (Baum et al, 2014;Short & Louca, 2015;Short et al, 2011). Perhaps our sample of adolescents with ASD did not differ from the NT sample in the level of their self-reported symptoms of anxiety and depression in part because they benefitted from extra sleep.…”
Section: Discussionmentioning
confidence: 81%